2002
DOI: 10.1152/ajpregu.00011.2002
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of fatty acid oxidation mimics phase II-phase III transition in a fasting bird, the king penguin

Abstract: This study tests the hypothesis that the metabolic and endocrine shift characterizing the phase II-phase III transition during prolonged fasting is related to a decrease in fatty acid (FA) oxidation. Changes in plasma concentrations of various metabolites and hormones and in lipolytic fluxes, as determined by continuous infusion of [2-3 H]glycerol and [1-14 C]palmitate, were examined in vivo in spontaneously fasting king penguins in the phase II status (large fat stores, protein sparing) before, during, and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
2
18
1
Order By: Relevance
“…However, the possibility that the effects of increased basal glucagonemia could be different in some aspects from those of artificially raised glucagon levels should be examined, including using somatostatin (if effective in penguins) and replacement infusion of insulin. From previous results, we have suggested that under conditions of basal NEFA availability, entrance into phase III could be related to a decreased capacity for FA oxidation (3,4). In contrast, the present data suggest that oxidative capacity is maintained in phase III birds with highly increased NEFA availability.…”
Section: Perspectivescontrasting
confidence: 57%
See 1 more Smart Citation
“…However, the possibility that the effects of increased basal glucagonemia could be different in some aspects from those of artificially raised glucagon levels should be examined, including using somatostatin (if effective in penguins) and replacement infusion of insulin. From previous results, we have suggested that under conditions of basal NEFA availability, entrance into phase III could be related to a decreased capacity for FA oxidation (3,4). In contrast, the present data suggest that oxidative capacity is maintained in phase III birds with highly increased NEFA availability.…”
Section: Perspectivescontrasting
confidence: 57%
“…The specific activities of plasma glycerol and NEFA were determined as previously described (4,5). A 1-ml aliquot of plasma was mixed with chloroform-methanol (2:1, vol/vol).…”
Section: Determination Of Glycerol and Palmitate Specific Activitiesmentioning
confidence: 99%
“…For example, a dramatic change in fatty acid oxidation and BUN, prolactin and glucagon concentrations occur at the same time as elevated GC levels in animals on entry into phase III (Bernard et al, 2002a;Bernard et al, 2002b;Cherel et al, 1988a;Cherel et al, 1988b;Cherel et al, 1988c;Groscolas and Robin, 2001;Le Maho et al, 1981;Robin et al, 1998). Our findings do not exclude the possibility that cortisol provides a cue to forage in seals when fat reserves are very low, such as in starvelings.…”
Section: Discussionmentioning
confidence: 58%
“…Overall, body size effects on metabolic rate can only explain <50% of these large differences [calculated using the classic allometric equation for resting mammals (Schmidt-Nielsen, 1990)]. Lipolytic rate is also one order of magnitude higher in sandpipers than in king penguins (Bernard et al, 2002a;Bernard et al, 2002b;Bernard et al, 2003), the only other avian species measured to date. In addition, it is clear that the values of R a glycerol reported here lie at the lower end of the range of lipolytic rates achievable by ruff sandpipers for several reasons: (1) migration flights would simply not be possible without activating lipolysis well beyond the rates measured in this study (see next paragraph); (2) the animals used here were not physiologically prepared for migration (Vaillancourt et al, 2005) and they were not acclimated to hypoxia (a treatment known to stimulate lipolytic rate) (McClelland et al, 2001); (3) ruff sandpipers were measured here only 1-5·h after the cessation of feeding whereas all the mammalian species mentioned in Fig.·5 for comparison were fasted for much longer durations (18-24·h); and (4) it has been suggested that incomplete hydrolysis of triacylglycerol may take place in bird adipose tissue (Goodridge and Ball, 1965), and significant production of mono-and diacylglycerol in bird adipocytes would make R a glycerol underestimate true lipolytic rate (a situation that does not exist in mammals) (Brooks et al, 1982).…”
Section: Unusually High Lipolytic Rates In Migrant Birdsmentioning
confidence: 99%
“…The mean value plotted here for ruff sandpipers is for shivering birds (note that the mean value for non-shivering birds was even higher, although not significantly so; see Table·1). Each point is the mean value from a different study [rat (Kalderon et al, 2000;McClelland et al, 2001), rabbit (HimmsHagen, 1968;Reidy and Weber, 2002), dog Shaw et al, 1975), pigmy goat (Weber et al, 1993), sheep (Bergman, 1968), human (Bahr et al, 1990;Mora-Rodriguez et al, 2001;Wolfe et al, 1990) and king penguin (Bernard et al, 2002a;Bernard et al, 2002b;Bernard et al, 2003) . Assuming that 84% of the necessary ATP is derived from lipid oxidation (i.e.…”
Section: Unusually High Lipolytic Rates In Migrant Birdsmentioning
confidence: 99%